The Influence of Family Economic Education, Lifestyle On Consumption Behavior Through Economic Literacy In FEB UM Students - Andi Wisnu Murti; Sri Umi Mintarti Widjaja; Wening Patmi Rahayu (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
This study aims to examine the influence between variables whether there is a direct or indirect effect between the independent (exogenous) variables on the (endogenous) variables. This study uses a quantitative approach using data analysis techniques, namely SEM (Structural Equation Model) analysis. The population of this study were all FEB UM students, totaling 1118. The sample in this study were 295 respondents consisting of FEB UM students class of 2020. The sampling technique used a proportional random sampling technique, which is a random technique that is balanced and proportional to the number of subjects. Data collection techniques with questionnaires, and documentation. The results of this study indicate that there is a positive and significant influence of family economics education on the economic literacy of 2020 FEB UM students. There is a positive and significant influence of lifestyle on the economic literacy of 2020 FEB UM students. There is a positive and significant influence of family economics education on consumption behavior in 2020 UM FEB students. There is a positive and significant influence of lifestyle on consumption behavior in 2020 UM FEB students. There is a positive and significant influence of economic literacy on the consumption behavior of FEB UM 2020 students. There is an indirect positive and significant effect of family economics education on consumption behavior through the economic literacy of 2020 FEB UM students. There is an indirect positive and significant influence of family lifestyle on consumption behavior through the economic literacy of 2020 FEB UM students, so the seventh hypothesis is accepted .